Histamine Receptor 3 negatively regulates oligodendrocyte differentiation and remyelination. - Yongfeng Chen; Wei Zhen; Tony Guo; Yonggang Zhao; Ailian Liu; Justin P Rubio; David Krull; Jill C Richardson; Hongtao Lu; Ryan Wang (PLoS ONE, 2017)
Agents promoting oligodendrocyte precursor cell differentiation have the potential to restore halted and/or delayed remyelination in patients with multiple sclerosis. However, few therapeutic targets have been identified. The objective of this study was to identify novel targets for promotion of remyelination and characterize their activity in vitro and in vivo.A high-content screening assay with differentiation of primary rat oligodendrocyte precursor cells was used to screen GSK-proprietary annotated libraries for remyelination-promoting compounds. Compounds were further validated in vitro and in vivo models; clinical relevance of target was confirmed in human post-mortem brain sections from patients with MS.Of ~1000 compounds screened, 36 promoted oligodendrocyte precursor cell differentiation in a concentration-dependent manner; seven were histamine receptor-3 (H3R) antagonists. Inverse agonists of H3R but not neutral antagonists promoted oligodendrocyte precursor cell (OPC) differentiation. H3R was expressed throughout OPC differentiation; H3R expression was transiently upregulated on Days 3-5 and subsequently downregulated. H3R gene knockdown in OPCs increased the expression of differentiation markers and the number of mature oligodendrocytes. Overexpression of full-length H3R reduced differentiation marker expression and the number of mature cells. H3R inverse agonist GSK247246 reduced intracellular cyclic AMP (cAMP) and downstream cAMP response element-binding protein (CREB) phosphorylation in a dose-dependent manner. Histone deacetylase (HDAC-1) and Hes-5 were identified as key downstream targets of H3R during OPC differentiation. In the mouse cuprizone/rapamycin model of demyelination, systemic administration of brain-penetrable GSK247246 enhanced remyelination and subsequently protected axons. Finally, we detected high H3R expression in oligodendroglial cells from demyelination lesions in human samples of patients with MS, and validated a genetic association between an exonic single nucleotide polymorphism in HRH3 and susceptibility to multiple sclerosis.From phenotypic screening to human genetics, we provide evidence for H3R as a novel therapeutic target to promote remyelination in patients with multiple sclerosis.